Perceived organizational performance and trust in project manager and top management in project-based organizations: Comparative analysis using statistical and grey systems methods. Issue 3 (28th June 2018) - Javed, Saad Ahmed; Syed, Ali Murad; Javed, Sara
Abstract : Purpose: The purpose of this paper is to empirically analyze the effect of the relationship between trust in top management (TTM) and trust in immediate supervisor (TIS), who was organizational project manager in our case, on perceived organizational performance in Pakistani public and private project-based organizations (PBOs). Design/methodology/approach: The survey ( N =108) was done using a questionnaire that was sent to project managers in the selected PBOs in Pakistan with a request to forward it to their immediate subordinates. Later, established statistical techniques (correlation and regression analyses) and gray incidence analysis models were applied to test the hypotheses. Findings: The results from both methods reveal that TTM was more strongly correlated to perceived organizational performance of PBOs and, in general, public sector employees are more trusted than private sector employees. The gray method revealed that in both private and public PBOs, trust in project manager is greater predictor of perceived organizational performance, while statistical analysis confirmed this only for private sector PBOs. According to statistical analysis, the public sector employees who trust their top management are more likely to have good perception of the organizational performance. Later, the study argues that because of the proven superiority of gray methods over statistics on small samples, the results obtained from gray method should be used for decision making and implications. Originality/value: The study is pioneer in evaluating the association between TIS and TTM in PBOs using both statistical and gray systems methods.